Optimization of T Cell Redirecting Strategies: Obtaining Inspirations From Natural Process of T Cell Activation - Gao, Yiyuan; Wang, Yuedi; Luo, Feifei; Chu, Yiwei (Frontiers in Immunology, 2021)
Chimeric antigen receptors (CARs) or bispecific antibodies (bsAbs) redirected T cell against tumors is one of the most promising immunotherapy approaches. However, insufficient clinical outcomes are still observed in treatments of both solid and non-solid tumors. Limited efficacy and poor persistence are two major challenges in redirected-T cell therapies. The immunological synapse (IS) is a vital component in T cell response, which largely determines the clinical outcomes of T cell-based therapies. Here, we review the structural and signaling characteristics of IS formed by natural T cells and redirected-T cells. Furthermore, inspired by the elaborate natural T cell receptor-mediated IS, we provide potential strategies for enhancing the therapeutic efficacy and prolonging the persistence of redirected-T cells.